Observation method in assessing instructor performance: ISMEK case study - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
The purpose of this study is to measure the efficiency of the instructors' classroom management at the ISMEK, an organization of Istanbul Metropolitan Municipality. ISMEK is undoubtedly at the top of the list of the contributors of the adult education. ISMEK was founded in 1996 and as of 2012; it provides service to about 240.000 people annually in about 230 course centers. Therefore, it could be stated that ISMEK is fascinating in terms of its budget and the quality of the service it provides. In this study, it is aimed to assess the classroom performance of qualified instructors by using observation method. Classroom efficiency of the subjects were observed by expert supervisors, the findings were recorded in the assessment forms, then these forms were classified and interpreted after performing the necessary analyses. It was observed that, the older the instructors get, the more developed they become and the better they perform; and the longer they teach, the more efficient they become. It is also observed that their performance improve in parallel with their seniority. No significant difference was found for gender of the instructors. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: instructor; performance; observation method; ISMEK